2020
DOI: 10.1007/s11695-020-04913-6
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Erosive Esophagitis After Conversion from Vertical Sleeve Gastrectomy to Roux-en-Y Gastric Bypass

Abstract: Background Laparoscopic sleeve gastrectomy (LSG) has become the preferred bariatric procedure in many countries. However, there is one shortcoming of LSG in the long-term follow-up, and this is the onset of gastro-esophageal reflux disease (GERD) and erosive esophagitis (EE). Conversion to Roux-en-Y gastric bypass (RYGB) is considered an option in patients unresponsive to medical therapy. Currently, there is no evidence of EE improvement or resolution after conversion surgery. In this study, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
0
5
0
3
Order By: Relevance
“…The reported main symptoms are pain (27.3-44.7%), dysphagia (12.5%), respiratory symptoms (17%), and vomiting (12.5%). EE and Barrett´s esophagus have been observed in a wide range of percentage (2.4-10.6% and 0-17.6%, respectively) 5 , 7 , 13 , 20 , 23 , 27 , 28 , 29 , 31 , 33 , 34 , 39 , 40 , 41 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The reported main symptoms are pain (27.3-44.7%), dysphagia (12.5%), respiratory symptoms (17%), and vomiting (12.5%). EE and Barrett´s esophagus have been observed in a wide range of percentage (2.4-10.6% and 0-17.6%, respectively) 5 , 7 , 13 , 20 , 23 , 27 , 28 , 29 , 31 , 33 , 34 , 39 , 40 , 41 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Entre un 2% y un 12% de pacientes intervenidos de GV requerirán una segunda intervención por RGE severo. (1) Es frecuente que los pacientes obesos mórbidos presenten patología esofagogástrica como la gastritis o el reflujo gastroesofágico; que no siempre es sintomática y que puede afectar a la evolución tras la intervención (3). Por ello, el papel de la endoscopia y el tránsito baritado en el preoperatorio de la cirugía bariátrica es algo controvertido.…”
Section: Discussionunclassified
“…La aplicación de una técnica quirúrgica adecuada es probablemente el factor modificable más importante en la prevención de esta complicación (3). El BPG es en el momento actual la técnica de cirugía revisional más adecuada y ampliamente aceptada para tratar a los pacientes con ERGE severo tras gastrectomía vertical (3).…”
Section: Conclusionesunclassified
“…Although our unit’s questionnaire was not validated but was more relevant to post-sleeve gastrectomy subjects, it takes into account smoking and alcohol history, symptoms related to meals, PPI usage, overeating and differentiation between acid reflux versus volume reflux [ 25 ]. We found that commonly used validated questionnaires, such as GERD-Q and GERD health-related quality of life (GERD-HRQL), may be useful in correlating symptoms to presence of esophagitis, but extremely impractical to assess progression or response of symptoms over time.…”
Section: Discussionmentioning
confidence: 99%